Challenges of limited treatment options in suspected antimicrobial resistance of multibacillary Hansen's disease with chronic erythema nodosum leprosum: a case report and literature review - Agrevina Ane Lukito; I Ketut Suteja Wibawa; I Komang Harry Supradnyan (Explorer Front, 2025)
Background: Hansen's disease, or leprosy, is a chronic infection caused by Mycobacterium leprae that affects the skin and peripheral nerves. The emergence of antimicrobial resistance in leprosy poses a new challenge, potentially reducing treatment efficacy and increasing the risk of relapse. Recent studies report recurrent or chronic erythema nodosum leprosum (ENL) cases linked to relapse caused by drug-resistant Mycobacterium leprae strains. This case report aimed to emphasize the knowledge and therapeutic approach of leprosy and leprosy reaction. Case Description: A 51-year-old female patient previously treated for multibacillary (MB) leprosy and declared released from treatment (RFT) a year earlier, presented with painful erythematous nodules on all extremities two months after RFT. Eight months after RFT, the patient developed new erythematous macules with loss of sensation on all extremities, consistent with leprosy relapse. Multi-drug therapy (MDT) was subsequently re-initiated. During follow-up, laboratory evaluation indicated a high bacterial load, raising suspicion of antimicrobial resistance. The patient was initiated on the regimen for leprosy with antimicrobial resistance. However, the complete regimen could not be provided immediately due to medication limitations in the remote region. Conclusion: Antimicrobial resistance in leprosy should be considered in patients with relapse who do not respond to MDT re-treatment and in those with chronic ENL. Limited availability of resistance testing resources and access to second-line therapies remain a significant barrier to the effective management of antimicrobial resistance leprosy.